Vico's Ring. Notes on the"Scienza nuova", its Structure, and the Hermeneutics of Homer's Works - Horst STEINKE (I Quaderni del LAB, 2016)
The present study of Giambattista Vico's defining work, La Scienza nuova (The New Science) is concerned with an approach to the work that pays requisite attention not only to the content but also to its form. To that end, Horst Steinke proposes that Scienza nuova possesses the structure of a ring composition by which individual parts of the work relate to each other in complex but identifiable ways. This approach, which is developed through a discussion of all five Books that make up the work, also leads to, or implies, certain constraints on the interpretation of Vico's thought, resulting from an interplay of form and content. Since Vico made Homer the centerpiece of his own work, Vico's hermeneutics are discussed in the context of his underlying philosophy of language, and both are compared with Spinoza's thought. Finally, the so-called "Homeric question", in Vico's view, is addressed in an original way.